Алгоритм навчання систем термінального керування з підвищеною швидкістю збіжності - Кучеров, Д. П.; Коров’яков, А. Б. (Видавництво Львівської політехніки, 2011)
In this report the algorithm of training of system of terminal control based on application of methods multiple estimation, dot identification and training of pattern recognition is offered. The algorithm differs by the improved speed of convergence. The results of modeling are given.
Keywords: навчання розпізнаванню образів; точкова ідентифікація; множинне оцінювання; термінальне керування